Deprivation, subjective well-being, frustration and tendency of aggressive behavior among youth inmates in a prison in Nigeria - Yusuf, Ibrahim (2017)
This study examines deprivation, subjective well-being, frustration and tendency of aggressive behavior among youth inmates in Sokoto State central prison, Nigeria. Several factors contribute to the aggressive behavior identified, such as deprivation, frustration and low subjective well-being. Aggressive behavior has posed a serious challenge not only to the youth inmates, but to the prison authority, other relevant authorities and the community as well. The prime aim of establishing prisons is to rehabilitate and reformed inmates, but such objective has not been adequately realized. This is due to the fact that most of the Nigerian prisons are constantly aching from the problem of deprivation, low subjective well-being and frustration, which trigger aggressive behavior. The purpose of this study is to illustrate the background of the respondent (ii) The level of deprivation, subjective well-being, aggressive behavior, and frustration among the youth inmates. (iii) The differences in the level of deprivation, subjective well-being, aggressive behavior and frustration based on the background of the inmates. (iv) The relationships between deprivation, subjective well-being, aggressive behavior and frustration among inmates. (v) To determine the factors that contribute significantly to aggressive behavior. (vii) To determine the mediating role of subjective well-being and frustration in the relationship between deprivation and aggressive behavior. The study used quantitative approaches. A total of 312 responses was successfully collected from the male prison inmates. The data were analyzed through the use of SPSS Software using both descriptive and inferential statistics. The result of the descriptive analysis of the level of the tendency of aggressive behavior showed that out of the 300 respondents, 214 (71.3%) were found to exhibit the high tendency of aggressive behavior. A high level of deprivation 257 (85.7%) among the inmates. A low level of subjective well-being (84%) and a high level of frustration (79.%). The finding indicated that there is no significant difference in deprivation, frustration and tendency of aggressive behavior among the tribe, religion, occupation, and state. However, the finding also indicated that there is a significant difference between age groups, duration of stay educational qualification, the status of conviction and marital status. Moreover, the study also shows that there is a significant relationship between frustration and tendency of aggressive behavior and between deprivation and tendency of aggressive behavior. The finding also reveals a significant negative relationship between subjective well-being and aggressive behavior. The finding also showed that deprivation, subjective well-being, and frustration significantly contributes to the tendency of aggressive behavior among inmates. The finding also reveals, that there is a mediating effect of frustration on the relationship between deprivation and aggressive behavior tendency.